If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(6x + 3) = 0 Reorder the terms: 9(3 + 6x) = 0 (3 * 9 + 6x * 9) = 0 (27 + 54x) = 0 Solving 27 + 54x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 54x = 0 + -27 Combine like terms: 27 + -27 = 0 0 + 54x = 0 + -27 54x = 0 + -27 Combine like terms: 0 + -27 = -27 54x = -27 Divide each side by '54'. x = -0.5 Simplifying x = -0.5
| 7x=11x+16 | | 3x+-7=-8 | | 9a-4a+a-10= | | 6w+5=w-35 | | 3(2t^2-5)=t | | -5x+-5=9x | | a^2x^2-8abx+16b^2=0 | | 97-4x=41x+17 | | 9=a(14) | | 11-10x=40-17x | | 10x+35=28x+35 | | -74-9x=7x+22 | | 8p-24+10p=138 | | 19r=304 | | 2x+10=-20-8x | | 9a=14 | | 3x-4-x=2x-4 | | r-17=20 | | 124-6x=2x+20 | | 2x+(4x+1)=15 | | 3x-8=0 | | 28+2n=14 | | -9x+15=-22-4(x+22) | | 2x+7(.5)=2 | | 10+8x=4x+16 | | 12h=156 | | -3-6x=6-7x | | 4h(2+6h)= | | 8x^2+33x-35= | | 10=2x-3 | | 12=156h | | -4x-32=-72 |